Absolute Determination of the Electrochemical Equivalent and the Atomic Weight of Zinc II. Final Determination - Marinenko, George (J Res Natl Bur Stand A Phys Chem, 1975)
A new, successful approach to the determination of atomic weights of suitable elements has been demonstrated in this research. An absolute constant-current coulometric method was employed for the determination of the electrochemical equivalent and the atomic weight of zinc. The effects of possible sources of systematic error were investigated and appropriate corrections applied. The newly determined values of the two constants are 0.3387958 mg C(−1) and 65.3771 respectively. The uncertainty in the atomic weight of zinc was reduced by more than an order of magnitude. The publication of partial data resulted in the revision of the value of the atomic weight of zinc by the International Union of Pure and Applied Chemistry.